Analisis Tingkat Kepuasan Masyarakat Terhadap Realisasi Pelaksanaan Rencana Pembangunan Jangka Menengah Desa Air Genting Kecamatan Air Batu Kabupaten Asahan - Jaroddi Jaroddi; Satria Tirtayasa; Hazmanan Khair (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of this study is to determine and analyze the level of community satisfaction as measured by reality (tangiable), reliability, responsiveness, assurance, empathy (empathy for the realization of the implementation of RPJMDes and analyze priority strategies in increasing community satisfaction). to the realization of the implementation of RPJMDes in Air Genting Village, Asahan Regency. This study used a descriptive and verification approach. The population of this study was a village community with criteria aged 16-55 years of 4,543 people. The sample of this study used the Slovin formula as many as 100 respondents. through a questionnaire (questionnaire) that has been tested for validity and reliability. Data analysis used in this study using Microsoft Excel 2010 and SPSS version 20 with analysis of the Level of Conformity Index and Cartesian diagram. ba h that the level of satisfaction of the Air Genting community is categorized as important. The results of the Cartesian diagram show that 14 attributes occupy the B quadrant which must be maintained.